ESB Technology and Innovation extending web services with asynchronous message delivery and intelligent routing. - Davies, Robert
Called to larger tasks, messaging technology is now in a phase of evolution. A mixed message model is needed to combine the best of Web services and traditional asynchronous message delivery to provide the flexibility required for today's real-time enterprise.